A straightforward wet-chemical route to the nanocomposites of general layered clays and metal sulfides - Han, Zhaohui; Zhu, H.; Shi, J.; Lu, G. (Elsevier Science, 2006)
The nanocomposites of general layered clays and metal sulfides could be produced from reactions of the layered clay aqueous suspensions and water-soluble metal–thiourea complexes. The clay could be saponite, montmorillonite, hectorite and laponite, while the metal sulfide could be cobalt sulfide, nickel sulfide, zinc sulfide, cadmium sulfide, and lead sulfide. In the nanocomposites, the clay could be incorporated with the metal sulfide pillars and metal sulfide nanoparticles.